2016
DOI: 10.1016/j.appet.2015.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Eating dinner away from home: Perspectives of middle-to high-income parents

Abstract: This study sought to understand barriers and facilitators for preparing and eating dinner at home in families who report eating dinner away from home ≥3 per week. Cross-sectional, mixed methods (focus groups, questionnaires) study. Twenty-seven parents with a child 3–10 years-old who reported eating dinner away from home ≥3 times per week from a pediatric medical center in the Midwest participated. The key concepts analytic framework guided focus group analysis. Descriptive statistics were used to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 33 publications
(51 reference statements)
1
42
0
Order By: Relevance
“…Rather, a diet low in fruit and vegetables intake, observed in children with employed parents, may be due to the higher disposable income of family. Indeed, previous studies showed that higher household income is positively associated with both a higher consumption of meals outside home and convenience foods (Robson et al 2016), food habits often related to a poor diet quality and a greater energy intake (Nago et al 2014;Powell and Nguyen 2013). As for the unhealthy habits exhibited by children of highly educated parents, it may be correlated to highly demanding parental jobs which may leave less time to meals preparation as well as less control over what children eat at home.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, a diet low in fruit and vegetables intake, observed in children with employed parents, may be due to the higher disposable income of family. Indeed, previous studies showed that higher household income is positively associated with both a higher consumption of meals outside home and convenience foods (Robson et al 2016), food habits often related to a poor diet quality and a greater energy intake (Nago et al 2014;Powell and Nguyen 2013). As for the unhealthy habits exhibited by children of highly educated parents, it may be correlated to highly demanding parental jobs which may leave less time to meals preparation as well as less control over what children eat at home.…”
Section: Resultsmentioning
confidence: 99%
“…Despite shifting domestic roles, mothers remain principal family food providers. Time spent working could influence the number of meals cooked and consumed at home, thus placing a heavy emphasis on meals and snacks away from home or on prepackaged, ready-to-eat foods, which are often of lower nutritional quality (Robson, Crosby, & Stark, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…HETs believed that home economics is the logical and most favourable place where food literacy could be taught comprehensively because it incorporates a theoretical and most importantly practical component which allows adolescents to develop food skills which aligns with findings of other studies (Slater, 2013;Benn, 2014;Colatruglio and Slater, 2014). It is important more than ever to build adolescents' food skills as many are experiencing reduced exposure to food skills within the home environment associated with increased consumption of convenience foods and parents having low levels of food literacy (Robson et al, 2016). HETs observed that many adolescents undertaking home economics classes have little knowledge of food, food preparation and food-related hygiene practices.…”
Section: Discussionmentioning
confidence: 99%